Rational expectations and econometric practice - Lucas, Robert E., Jr; Sargent, Thomas J. (University of Minnesota Press, 1981)
Assumptions about how people form expectations for the future shape the properties of any dynamic economic model. To make economic decisions in an uncertain environment people must forecast such variables as future rates of inflation, tax rates, governme.